1989
DOI: 10.1288/00005537-198904000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of syncope from head and neck cancer

Abstract: Five patients suffering from recurrent syncope in association with metastatic squamous cell carcinoma of the head and neck were examined. Two patients had exhaustive diagnostic work-up for syncope, which eventually disclosed previously undiagnosed, recurrent squamous cell carcinoma. Case reports describe glossopharyngeal neuralgia, a well recognized cause of syncope in the head and neck cancer patient, characterized by acute unilateral head or neck pain preceding each syncopal episode. The literature on the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Carotid sinus compression by a neck mass or the invasion of the tumor in patients with head and neck cancer can cause episodes of bradycardia and intermittent pauses. Carotid body tumors, local tumors such as thyroid cancers, cervical lymphadenopathy, postradiation fibrosis, and internal carotid artery aneurysms, are known to cause carotid sinus sensitivity [ 5 7 ]. Although the pathophysiology of this process is well-characterized, it is suggested to be associated with a permanent depolarization of neuronal axons with an increased sensitivity to impulses.…”
Section: Discussionmentioning
confidence: 99%
“…Carotid sinus compression by a neck mass or the invasion of the tumor in patients with head and neck cancer can cause episodes of bradycardia and intermittent pauses. Carotid body tumors, local tumors such as thyroid cancers, cervical lymphadenopathy, postradiation fibrosis, and internal carotid artery aneurysms, are known to cause carotid sinus sensitivity [ 5 7 ]. Although the pathophysiology of this process is well-characterized, it is suggested to be associated with a permanent depolarization of neuronal axons with an increased sensitivity to impulses.…”
Section: Discussionmentioning
confidence: 99%
“…Muntz and Smith in 1983 postulated that a tumor located near the Carotid Sinus or it’s nerve could cause a permanent depolarization of its axons with an increased tendency of adjacent uninjured axons to fire impulses causing signs and symptoms of CSS [ 19 ]. Radiation therapy of the carotid sinus has often been used to treat malignancies of the head and neck region, but some case series have described it as a cause of CSH (by post-irradiation fibrosis) by a mechanism similar to the one just described [ 20 ]. Wallin and Westerberg suggested that syncope in these patients is caused by abnormal impulses that are rerouted via the pharynx to the dorsal motor nucleus of vagus, causing excitation of the vagus [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of reports of carotid sinus syndrome associated with head and neck malignancy relate to extensive nodal involvement in the neck [14]. …”
Section: Discussionmentioning
confidence: 99%